2022
DOI: 10.7341/20221815
|View full text |Cite
|
Sign up to set email alerts
|

The impact of common success factors on overfunding in reward-based crowdfunding: An explorative study and avenues for future research

Abstract: PURPOSE: While there is abundant literature on the key determinants of reward-based crowdfunding success, little research is dedicated to crowdfunding projects that are not only successful but receive significantly more funds than initially targeted through the defined funding goal. This study seeks to shed light on this vastly neglected topic in crowdfunding research. METHODOLOGY: Drawing on a rich dataset of 338 rewardbased crowdfunding projects, this study applied a two-step statistical analysis. First, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Individual investors lack the financial literacy of "valuation." Other results were generally consistent with Tables 12, 13, and Pinkow (2022) showed that factors affecting project success/failure differ from those affecting fundraising rate (overfunding). In Japanese ECF, project success/failure and fundraising rate are expected to be affected by almost the same factors.…”
Section: Robustness Checksupporting
confidence: 86%
“…Individual investors lack the financial literacy of "valuation." Other results were generally consistent with Tables 12, 13, and Pinkow (2022) showed that factors affecting project success/failure differ from those affecting fundraising rate (overfunding). In Japanese ECF, project success/failure and fundraising rate are expected to be affected by almost the same factors.…”
Section: Robustness Checksupporting
confidence: 86%
“…Research shows that the majority of rewards-based crowdfunding projects do not reach their target funding goal, whereas those that do exceed the goal do so by only a small amount (Mollick, 2014). Therefore, Pinkow (2022) emphasizes the need to focus specifically on projects that receive funding above their intended goal. These projects can shed the most light on the factors that matter most when it comes to achieving successful projects from the creators’ perspective.…”
Section: Methodsmentioning
confidence: 99%
“…These projects can shed the most light on the factors that matter most when it comes to achieving successful projects from the creators’ perspective. Whereas some researchers have studied “overfunding” (Li et al , 2020; Weber et al , 2023), work addressing this outcome remains sparse (Pinkow, 2022). Above-goal funding creates slack resources for creators, which can enable postfundraising execution (Weber et al , 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Other results were generally consistent with Tables 12, 13, and Table 14 Model 1. A study on reward-based crowdfunding conducted by Pinkow (2022) showed that factors affecting project success/failure differ from those affecting fundraising rate (overfunding). In Japanese ECF, project success/failure and fundraising rate are expected to be affected by almost the same factors.…”
Section: Robustness Checkmentioning
confidence: 99%